Methane Source and Turnover in the Shallow Sediments to the West of Haima Cold Seeps on the Northwestern Slope of the South China Sea - Junxi Feng; Shengxiong Yang; Hongbin Wang; Jinqiang Liang; Yunxin Fang; Min Luo (Geofluids)
The Haima cold seeps are active cold seep areas that were recently discovered on the northwestern slope of the South China Sea (SCS). Three piston cores (CL30, CL44, and CL47) were collected within an area characterized by bottom simulating reflectors to the west of Haima cold seeps. Porewater profiles of the three cores exhibit typical kink-type feature, which is attributed to elevated methane flux (CL30) and bubble irrigation (CL44 and CL47). By simulating the porewater profiles of SO42-, CH4, PO43-, Ca2+, Mg2+, and dissolved inorganic carbon (DIC) in CL44 and CL47 using a steady-state reaction-transport model, we estimated that the dissolved SO42- was predominantly consumed by anaerobic oxidation of methane (AOM) at rates of 74.3 mmol m−2 yr−1 in CL44 and 85.0 mmol m−2 yr−1 in CL47. The relatively high AOM rates were sustained by free gas dissolution rather than local methanogenesis. Based on the diffusive Ba2+ fluxes and the excess barium contents in the sediments slightly above the current SMTZ, we estimated that methane fluxes at core CL44 and CL47 have persisted for ca. 3 kyr and 0.8-1.6 kyr, respectively. The non-steady-state modeling for CL30 predicted that a recent increase in upward dissolved methane flux was initiated ca. 85 yr ago. However, the required time for the formation of the barium front above the SMTZ at this core is much longer (ca. 2.2-4.2 kyr), which suggests that the depth of SMTZ possibly has fluctuated due to episodic changes in methane flux. Furthermore, using the model-derived fractions of different DIC sources and the δ13CDIC mass balance calculation, we estimated that the δ13C values of the external methane in cores CL30, CL44, and CL47 are -74.1‰, -75.4‰, and -66.7‰, respectively, indicating the microbial origin of methane. Our results suggest that methane seepage in the broader area surrounding the Haima cold seeps probably has persisted at least hundreds to thousands of years with changing methane fluxes.